Composite solid electrolyte material and method for preparing the same
Patent Information
- Application Number
- CN202611303968.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-30
AI Technical Summary
本发明的目的在于提供一种复合固态电解质材料及其制备方法,以解决现有复合固态电解质中离子电导率偏低、锂离子迁移数不高以及循环过程中容量保持率不足的问题
(1)本发明对钽掺杂锂镧锆氧填料依次进行酸活化、硅烷偶联和聚醚链段接枝处理,在填料表面共价连接含丙烯酸酯基团的聚醚链段。接枝的聚醚链段与聚环氧乙烷基体化学结构同源,在成膜过程中能够发生链缠结渗透,使填料在基体中实现均匀分散并形成紧密的界面过渡层,有效降低了填料与基体间的界面阻抗,提升了复合电解质的离子电导率。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte technology, specifically to a composite solid electrolyte material and its preparation method. Background Technology
[0002] Liquid lithium-ion batteries pose safety hazards such as leakage and combustion due to the use of flammable organic electrolytes. Replacing liquid electrolytes with solid-state electrolytes can fundamentally improve battery safety. Solid-state electrolytes are mainly divided into two categories: inorganic ceramic electrolytes and polymer electrolytes. Inorganic ceramic electrolytes have high room-temperature ionic conductivity, but suffer from brittleness, poor contact with the electrode interface, and high preparation temperatures. Polymer electrolytes offer good flexibility, are easy to process, and have good contact with the electrode interface, but their low room-temperature ionic conductivity limits practical applications. Combining inorganic fillers with a polymer matrix to prepare organic-inorganic composite solid-state electrolytes is an effective way to balance ionic conductivity and flexibility.
[0003] There are existing reports on composite solid electrolytes. Chinese Patent 202610278229.4 discloses a solid electrolyte sheet and its preparation method. The electrolyte sheet is prepared from the following raw materials in parts by weight: 60-85 parts lithium salt, 10-25 parts composite inorganic filler, 3-10 parts polymer matrix, 0.5-3 parts compatibilizer, and 0.1-1 parts antioxidant. This technical solution uses lithium salt as the main component and improves the overall performance of the electrolyte sheet by introducing composite inorganic filler and compatibilizer. However, in this technical solution, the interfacial bonding between the inorganic filler and the polymer matrix mainly relies on the physical effect of the compatibilizer, lacking interfacial anchoring at the chemical bonding level. During long-term battery cycling, interfacial separation may occur between the filler and the matrix, affecting the cycling stability of the electrolyte sheet.
[0004] In polymer-based composite solid electrolyte research, polyethylene oxide (PEO) and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFA) are commonly used polymer matrix materials. Adding inorganic fillers can reduce polymer crystallinity and construct interfacial ion conduction pathways, while adding plasticizers can further enhance chain segment mobility. The type, morphology, and surface state of the inorganic filler have a significant impact on the performance of the composite electrolyte. The uniformity of filler dispersion and the interfacial bonding state in the polymer matrix directly affect ion conduction efficiency and cycle stability. Achieving effective interfacial bonding between the filler and the polymer matrix is a key issue in composite solid electrolyte research. Summary of the Invention
[0005] (a) Technical problems to be solved The purpose of this invention is to provide a composite solid electrolyte material and its preparation method to solve the problems of low ionic conductivity, low lithium-ion transference number, and insufficient capacity retention during cycling in existing composite solid electrolytes.
[0006] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: A composite solid electrolyte material comprises the following raw materials in parts by weight: 60-85 parts polyethylene oxide, 5-15 parts modified filler, 10-30 parts modified lithium salt, and 1-10 parts succinic anionyl nitrile. Furthermore, the modified filler is prepared by means of the following steps: A1. Tantalum-doped lithium lanthanum zirconium oxide was dispersed in hydrochloric acid aqueous solution, ultrasonically treated, centrifuged, washed with deionized water until neutral, and vacuum dried to obtain activated filler; A2. Under nitrogen protection, the activated filler was dispersed in anhydrous toluene, 3-propyltriethoxysilane and dibutyltin dilaurate were added, the mixture was stirred and reacted, centrifuged under nitrogen protection, and washed with anhydrous toluene to obtain the coupling intermediate; A3. Disperse the coupling intermediate in dry N,N-dimethylformamide, add hydroxyl-polyethylene glycol-acrylate, stir and react, separate by centrifugation, wash with N,N-dimethylformamide, and vacuum dry to obtain the modified filler; Furthermore, the modified lithium salt is prepared by the following steps: B1. Under a nitrogen atmosphere, 4-vinylbenzenesulfonamide was dissolved in anhydrous tetrahydrofuran, cooled in an ice bath, and sodium hydride was added in portions. After the addition was complete, the mixture was heated to room temperature and stirred to obtain the active precursor. B2. Add an anhydrous N,N-dimethylformamide solution of 1,3-propanesulfonic acid lactone to the active precursor, heat and stir the reaction, cool, filter, and dry to obtain the sulfonated intermediate; B3. The sulfonated intermediate is suspended in deionized water, lithium carbonate is added, the mixture is stirred at room temperature, filtered, the filtrate is concentrated under reduced pressure and dried under vacuum to obtain the modified lithium salt.
[0007] Furthermore, in step A1, the tantalum-doped lithium lanthanum zirconium oxide particle size D50 is 200-800 nm, the specific surface area is 2-10 m² / g, and the ionic conductivity is not less than 1×10⁻⁶. -4 S / cm.
[0008] Furthermore, in step A1, the concentration of the hydrochloric acid aqueous solution is 0.1-1.0 mol / L, the ultrasonic treatment time is 30-60 min, the vacuum drying temperature is 120-150℃, the time is 2-4 h, and the solid-liquid ratio of tantalum-doped lithium lanthanum zirconium oxide to hydrochloric acid aqueous solution is 1:(20-50).
[0009] Furthermore, in step A2, the temperature of the stirring reaction is 60-80℃, the time is 4-8h, the solid-liquid ratio of the activated filler to anhydrous toluene is 1:(20-40), the amount of 3-propyltriethoxysilane used is 5-15wt% of the mass of the activated filler, and the amount of dibutyltin dilaurate used is 0.1-1.0wt% of the mass of 3-propyltriethoxysilane.
[0010] Furthermore, in step A3, the stirring reaction is carried out at a temperature of 50-70°C for 6-12 hours, the vacuum drying is carried out at a temperature of 40-60°C for 12-24 hours, the solid-liquid ratio of the coupling intermediate to N,N-dimethylformamide is 1:(10-30), and the amount of hydroxyl-polyethylene glycol-acrylate is 10-30 wt% of the mass of the coupling intermediate.
[0011] Furthermore, in step B1, the amount of sodium hydride used is 13-14 wt% of the mass of 4-vinylbenzenesulfonamide, the amount of anhydrous tetrahydrofuran used is 8-15 times the mass of 4-vinylbenzenesulfonamide, and the reaction time at room temperature is 2-4 h.
[0012] Furthermore, in step B2, the amount of 1,3-propanesulfonic acid lactone is 67-80 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, the amount of N,N-dimethylformamide is 3-6 times the mass of 1,3-propanesulfonic acid lactone, the temperature of the heated and stirred reaction is 40-60°C, and the time is 12-24 h.
[0013] Furthermore, in step B3, the amount of lithium carbonate used is 20-24 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, the stirring reaction time at room temperature is 2-4 h, and the vacuum drying temperature is 50-80 °C for 12-24 h.
[0014] A method for preparing a composite solid electrolyte material includes the following steps: S1. Dissolve polyethylene oxide, modified lithium salt, succinate and initiator in an organic solvent, stir to dissolve, and obtain a mixed solution; S2. Add the modified filler to the mixed solution and disperse it to obtain a slurry; S3. The slurry is cast onto a substrate, dried, and then peeled off to obtain the composite solid electrolyte material.
[0015] Furthermore, in step S1, the organic solvent is N,N-dimethylformamide, the initiator is azobisisobutyronitrile, the amount of initiator added is 0.1-2 wt% of the mass of polyethylene oxide, and the stirring and dissolving temperature is 30-50°C.
[0016] Furthermore, in step S3, the drying process is carried out at a temperature of 70-90°C for 12-20 hours and at a vacuum level of -0.08 to -0.1 MPa.
[0017] (iii) Beneficial technical effects Compared with the prior art, the beneficial effects of the present invention are: (1) In this invention, tantalum-doped lithium lanthanum zirconium oxide filler is subjected to acid activation, silane coupling, and polyether segment grafting treatment in sequence, and polyether segments containing acrylate groups are covalently connected to the filler surface. The grafted polyether segments are chemically homologous to polyoxyethylene esters, and can undergo chain entanglement and penetration during film formation, so that the filler is uniformly dispersed in the matrix and forms a tight interfacial transition layer, which effectively reduces the interfacial impedance between the filler and the matrix and improves the ionic conductivity of the composite electrolyte.
[0018] (2) In this invention, a sulfonylimide lithium salt containing styrene double bonds is used to partially replace conventional lithium salts. This modified lithium salt participates in the cross-linking reaction through the styrene double bonds under the action of an initiator, covalently anchoring the sulfonylimide anion in the polymer network. After the anion is fixed, lithium ions become the main charge carriers, significantly increasing the lithium ion transport number, effectively suppressing concentration polarization during charging and discharging, and improving the rate performance of the battery.
[0019] (3) In this invention, an initiator is pre-added to the slurry, which initiates an in-situ free radical copolymerization crosslinking reaction between the acrylate groups on the surface of the active filler and the styrene double bonds of the modified lithium salt during the drying and film-forming stage. This forms a crosslinking network with the modified filler as nodes, the modified lithium salt as anionic anchoring points, and the polyethylene oxide segments as the conductive framework. This chemical crosslinking network, together with the physical entanglement of the polyether segments, constitutes a dual interface anchoring structure, which enhances the mechanical strength and structural stability of the electrolyte membrane. During battery cycling, it can effectively suppress the interface delamination between the filler and the matrix, and significantly improve the cycle capacity retention rate.
[0020] (4) In this invention, the interfacial crosslinking of the modified filler and the anionic anchoring of the modified lithium salt have a synergistic effect in the in-situ crosslinking system. The acrylate groups on the surface of the modified filler and the styrene double bonds of the modified lithium salt undergo a copolymerization reaction under the action of an initiator, so that the chemical bonding between the filler and the matrix and the covalent anchoring of the anions are realized simultaneously in the same crosslinking network. The two functions enhance each other rather than being mutually exclusive, and the overall performance is better than the scheme that uses only a single modified component.
[0021] (5) The present invention uses succinic anhydride as a plasticizer. Its strong polar nitrile groups can effectively promote the dissociation of lithium salt and reduce the crystallinity of polyethylene oxide. Succinic anhydride is uniformly dispersed in the polymer matrix and works synergistically with polyether segments and crosslinking networks to provide more ion conduction pathways while maintaining the good flexibility of the electrolyte membrane, thereby further improving the ionic conductivity of the electrolyte.
[0022] (6) The acrylate groups and styrene double bonds contained in the modified filler and modified lithium salt of the present invention remain stable during the slurry preparation and casting stages, and only participate in the crosslinking reaction after the initiator decomposes during the drying stage. The entire process is simple to operate, the conditions are mild, and there is no need for high-temperature sintering or complex equipment, making it suitable for large-scale production. Detailed Implementation
[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0024] Example 1
[0025] A composite solid electrolyte material comprises the following raw materials in parts by weight: 60 parts polyethylene oxide, 5 parts modified filler, 10 parts modified lithium salt, and 1 part succinic anionyl nitrile. The modified filler is prepared by the following steps: A1. Tantalum-doped lithium lanthanum zirconium oxide was dispersed in hydrochloric acid aqueous solution, ultrasonicated at 100W for 60 min, centrifuged at 3000 rpm for 15 min, washed twice with deionized water until neutral, and vacuum dried at -0.1 MPa and 120℃ for 4 h to obtain activated filler; wherein the tantalum-doped lithium lanthanum zirconium oxide had a particle size D50 of 500 nm, a specific surface area of 5 m² / g, and an ionic conductivity of 3 × 10⁻⁶. -4 S / cm, the concentration of hydrochloric acid aqueous solution is 0.1mol / L, and the solid-liquid ratio of tantalum-doped lithium lanthanum zirconium oxide to hydrochloric acid aqueous solution is 1:50; A2. Under nitrogen protection, the activated filler was dispersed in anhydrous toluene, and 3-propyltriethoxysilane and dibutyltin dilaurate were added. The mixture was stirred at 200 rpm and reacted at 60°C for 8 h. Under nitrogen protection, the mixture was centrifuged at 3000 rpm for 15 min and washed twice with anhydrous toluene to obtain the coupling intermediate. The solid-liquid ratio of the activated filler to anhydrous toluene was 1:40, the amount of 3-propyltriethoxysilane was 5 wt% of the mass of the activated filler, and the amount of dibutyltin dilaurate was 0.1 wt% of the mass of 3-propyltriethoxysilane. A3. The coupling intermediate was dispersed in dry N,N-dimethylformamide, and hydroxyl-polyethylene glycol-acrylate was added. The mixture was stirred at 200 rpm and reacted at 50°C for 12 h. After centrifugation at 3000 rpm for 15 min, the mixture was washed twice with N,N-dimethylformamide and vacuum dried at -0.1 MPa and 40°C for 24 h to obtain the modified filler. The solid-liquid ratio of the coupling intermediate to N,N-dimethylformamide was 1:30, and the amount of hydroxyl-polyethylene glycol-acrylate was 10 wt% of the mass of the coupling intermediate. The modified lithium salt is prepared by the following steps: B1. Under a nitrogen atmosphere, 4-vinylbenzenesulfonamide was dissolved in anhydrous tetrahydrofuran, cooled to 0°C in an ice bath, and sodium hydride was added in portions at 10-minute intervals. After the addition was complete, the mixture was heated to room temperature and stirred at 200 rpm for 4 hours to obtain the active precursor. The amount of sodium hydride was 13 wt% of the mass of 4-vinylbenzenesulfonamide, and the amount of anhydrous tetrahydrofuran was 8 times the mass of 4-vinylbenzenesulfonamide. B2. Add an anhydrous N,N-dimethylformamide solution of 1,3-propanesulfonate lactone to the active precursor, stir at 200 rpm for 24 h at 40 °C, cool, filter, and dry at 50 °C for 12 h to obtain a sulfonated intermediate; wherein the amount of 1,3-propanesulfonate lactone is 67 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, and the amount of N,N-dimethylformamide is 3 times the mass of 1,3-propanesulfonate lactone; B3. The sulfonated intermediate is suspended in deionized water, lithium carbonate is added, and the mixture is stirred at room temperature for 4 hours at 200 rpm. The mixture is filtered, and the filtrate is concentrated under reduced pressure at 50°C. The filtrate is then vacuum dried at -0.1 MPa and 50°C for 24 hours to obtain the modified lithium salt. The amount of lithium carbonate used is 20 wt% of the mass of 4-vinylbenzenesulfonamide in step B1.
[0026] A method for preparing a composite solid electrolyte material includes the following steps: S1. Polyethylene oxide, modified lithium salt, succinate and initiator are dissolved in an organic solvent and stirred at 200 rpm for 4 h to obtain a mixed solution; wherein, the organic solvent is N,N-dimethylformamide, the initiator is azobisisobutyronitrile, the amount of initiator added is 0.1 wt% of the mass of polyethylene oxide, and the stirring and dissolving temperature is 30℃; S2. Add the modified filler to the mixed solution and ultrasonically disperse it at 100W power for 3 hours to obtain a slurry; S3. The slurry is cast onto a substrate, dried, and peeled off to obtain the composite solid electrolyte material; wherein the drying temperature is 70°C, the time is 20h, and the vacuum degree is -0.1MPa.
[0027] Example 2
[0028] A composite solid electrolyte material comprises the following raw materials in parts by weight: 66 parts polyethylene oxide, 8 parts modified filler, 15 parts modified lithium salt, and 3 parts succinic anionyl nitrile. The modified filler is prepared by the following steps: A1. Tantalum-doped lithium lanthanum zirconium oxide was dispersed in hydrochloric acid aqueous solution, ultrasonicated at 200W for 52 min, centrifuged at 4000 rpm for 12 min, washed three times with deionized water until neutral, and vacuum dried at -0.095 MPa and 128℃ for 3.5 h to obtain activated filler; wherein the tantalum-doped lithium lanthanum zirconium oxide had a particle size D50 of 500 nm, a specific surface area of 5 m² / g, and an ionic conductivity of 3 × 10⁻⁶. -4 S / cm, the concentration of hydrochloric acid aqueous solution is 0.3mol / L, and the solid-liquid ratio of tantalum-doped lithium lanthanum zirconium oxide to hydrochloric acid aqueous solution is 1:42; A2. Under nitrogen protection, the activated filler was dispersed in anhydrous toluene, and 3-propyltriethoxysilane and dibutyltin dilaurate were added. The mixture was stirred at 300 rpm and reacted at 65°C for 7 h. Under nitrogen protection, the mixture was centrifuged at 4000 rpm for 12 min and washed twice with anhydrous toluene to obtain the coupling intermediate. The solid-liquid ratio of the activated filler to anhydrous toluene was 1:35, the amount of 3-propyltriethoxysilane was 8 wt% of the mass of the activated filler, and the amount of dibutyltin dilaurate was 0.3 wt% of the mass of 3-propyltriethoxysilane. A3. The coupling intermediate was dispersed in dry N,N-dimethylformamide, and hydroxyl-polyethylene glycol-acrylate was added. The mixture was stirred at 300 rpm and reacted at 55°C for 10.5 h. After centrifugation at 4000 rpm for 12 min, the mixture was washed twice with N,N-dimethylformamide and vacuum dried at -0.095 MPa and 45°C for 21 h to obtain the modified filler. The solid-liquid ratio of the coupling intermediate to N,N-dimethylformamide was 1:25, and the amount of hydroxyl-polyethylene glycol-acrylate was 15 wt% of the mass of the coupling intermediate. The modified lithium salt is prepared by the following steps: B1. Under a nitrogen atmosphere, 4-vinylbenzenesulfonamide was dissolved in anhydrous tetrahydrofuran, cooled to 1°C in an ice bath, and sodium hydride was added in portions at 8-minute intervals. After the addition was complete, the mixture was heated to room temperature and stirred at 250 rpm for 3.5 h to obtain the active precursor. The amount of sodium hydride was 13.3 wt% of the mass of 4-vinylbenzenesulfonamide, and the amount of anhydrous tetrahydrofuran was 10 times the mass of 4-vinylbenzenesulfonamide. B2. Add an anhydrous N,N-dimethylformamide solution of 1,3-propanesulfonate lactone to the active precursor, stir at 45°C for 21 h with stirring at 250 rpm, cool, filter, and dry at 58°C for 10.5 h to obtain the sulfonated intermediate; wherein the amount of 1,3-propanesulfonate lactone is 70 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, and the amount of N,N-dimethylformamide is 4 times the mass of 1,3-propanesulfonate lactone; B3. The sulfonated intermediate is suspended in deionized water, lithium carbonate is added, and the mixture is stirred at room temperature for 3.5 h at 250 rpm. The mixture is filtered, and the filtrate is concentrated under reduced pressure at 55 °C. The filtrate is then vacuum dried at -0.095 MPa and 58 °C for 21 h to obtain the modified lithium salt. The amount of lithium carbonate used is 21 wt% of the mass of 4-vinylbenzenesulfonamide in step B1.
[0029] A method for preparing a composite solid electrolyte material includes the following steps: S1. Polyethylene oxide, modified lithium salt, succinate and initiator are dissolved in an organic solvent and stirred at 275 rpm for 3.2 h to obtain a mixed solution; wherein, the organic solvent is N,N-dimethylformamide, the initiator is azobisisobutyronitrile, the amount of initiator added is 0.6 wt% of the mass of polyethylene oxide, and the stirring and dissolution temperature is 35℃; S2. Add the modified filler to the mixed solution and ultrasonically disperse it for 2.5 hours at 200W power to obtain a slurry; S3. The slurry is cast onto a substrate, dried, and peeled off to obtain the composite solid electrolyte material; wherein the drying temperature is 75°C, the time is 18h, and the vacuum degree is -0.095MPa.
[0030] Example 3
[0031] A composite solid electrolyte material comprises the following raw materials in parts by weight: 72 parts polyethylene oxide, 10 parts modified filler, 20 parts modified lithium salt, and 5 parts succinic anionyl nitrile. The modified filler is prepared by the following steps: A1. Tantalum-doped lithium lanthanum zirconium oxide was dispersed in hydrochloric acid aqueous solution, ultrasonicated at 300W for 45 min, centrifuged at 5500 rpm for 10 min, washed three times with deionized water until neutral, and vacuum dried at -0.09 MPa and 135℃ for 3 h to obtain activated filler; wherein the tantalum-doped lithium lanthanum zirconium oxide had a particle size D50 of 500 nm, a specific surface area of 5 m² / g, and an ionic conductivity of 3 × 10⁻⁶. -4 S / cm, the concentration of hydrochloric acid aqueous solution is 0.5mol / L, and the solid-liquid ratio of tantalum-doped lithium lanthanum zirconium oxide to hydrochloric acid aqueous solution is 1:35; A2. Under nitrogen protection, the activated filler was dispersed in anhydrous toluene, and 3-propyltriethoxysilane and dibutyltin dilaurate were added. The mixture was stirred at 70°C for 6 hours at 400 rpm, and then centrifuged at 5500 rpm for 10 minutes under nitrogen protection. The mixture was washed three times with anhydrous toluene to obtain the coupling intermediate. The solid-liquid ratio of the activated filler to anhydrous toluene was 1:30, the amount of 3-propyltriethoxysilane was 10 wt% of the mass of the activated filler, and the amount of dibutyltin dilaurate was 0.5 wt% of the mass of 3-propyltriethoxysilane. A3. The coupling intermediate was dispersed in dry N,N-dimethylformamide, and hydroxyl-polyethylene glycol-acrylate was added. The mixture was stirred at 400 rpm and reacted at 60°C for 9 h. After centrifugation at 5500 rpm for 10 min, the mixture was washed three times with N,N-dimethylformamide and vacuum dried at -0.09 MPa and 50°C for 18 h to obtain the modified filler. The solid-liquid ratio of the coupling intermediate to N,N-dimethylformamide was 1:20, and the amount of hydroxyl-polyethylene glycol-acrylate was 20 wt% of the mass of the coupling intermediate. The modified lithium salt is prepared by the following steps: B1. Under a nitrogen atmosphere, 4-vinylbenzenesulfonamide was dissolved in anhydrous tetrahydrofuran, cooled to 2°C in an ice bath, and sodium hydride was added in portions at 7-minute intervals. After the addition was complete, the mixture was heated to room temperature and stirred at 300 rpm for 3 hours to obtain the active precursor. The amount of sodium hydride was 13.5 wt% of the mass of 4-vinylbenzenesulfonamide, and the amount of anhydrous tetrahydrofuran was 12 times the mass of 4-vinylbenzenesulfonamide. B2. Add an anhydrous N,N-dimethylformamide solution of 1,3-propanesulfonate lactone to the active precursor, stir at 50°C for 18 h with stirring at 300 rpm, cool, filter, and dry at 65°C for 9 h to obtain a sulfonated intermediate; wherein the amount of 1,3-propanesulfonate lactone is 74 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, and the amount of N,N-dimethylformamide is 4.5 times the mass of 1,3-propanesulfonate lactone; B3. The sulfonated intermediate is suspended in deionized water, lithium carbonate is added, and the mixture is stirred at room temperature for 3 hours at 300 rpm. The mixture is filtered, and the filtrate is concentrated under reduced pressure at 60°C. The filtrate is then vacuum dried at -0.09 MPa and 65°C for 18 hours to obtain the modified lithium salt. The amount of lithium carbonate used is 22 wt% of the mass of 4-vinylbenzenesulfonamide in step B1.
[0032] A method for preparing a composite solid electrolyte material includes the following steps: S1. Polyethylene oxide, modified lithium salt, succinate and initiator are dissolved in an organic solvent and stirred at 350 rpm for 2.5 h to obtain a mixed solution; wherein, the organic solvent is N,N-dimethylformamide, the initiator is azobisisobutyronitrile, the amount of initiator added is 1 wt% of the mass of polyethylene oxide, and the stirring and dissolving temperature is 40℃. S2. Add the modified filler to the mixed solution and ultrasonically disperse it at 300W power for 2 hours to obtain a slurry; S3. The slurry is cast onto a substrate, dried, and peeled off to obtain the composite solid electrolyte material; wherein the drying temperature is 80℃, the time is 16h, and the vacuum degree is -0.09MPa.
[0033] Example 4
[0034] A composite solid electrolyte material comprises the following raw materials in parts by weight: 78 parts polyethylene oxide, 13 parts modified filler, 25 parts modified lithium salt, and 8 parts succinic anionylene. The modified filler is prepared by the following steps: A1. Tantalum-doped lithium lanthanum zirconium oxide was dispersed in hydrochloric acid aqueous solution, ultrasonically treated for 38 min at 400 W, centrifuged at 7000 rpm for 8 min, washed with deionized water until neutral 4 times, and vacuum dried at -0.085 MPa and 142 °C for 2.5 h to obtain activated filler; wherein the tantalum-doped lithium lanthanum zirconium oxide had a particle size D50 of 500 nm, a specific surface area of 5 m² / g, and an ionic conductivity of 3 × 10⁻⁶. -4 S / cm, the concentration of hydrochloric acid aqueous solution is 0.8 mol / L, and the solid-liquid ratio of tantalum-doped lithium lanthanum zirconium oxide to hydrochloric acid aqueous solution is 1:28; A2. Under nitrogen protection, the activated filler was dispersed in anhydrous toluene, and 3-propyltriethoxysilane and dibutyltin dilaurate were added. The mixture was stirred at 75°C for 5 hours at 500 rpm, and then centrifuged at 7000 rpm for 8 minutes under nitrogen protection. The mixture was washed three times with anhydrous toluene to obtain the coupling intermediate. The solid-liquid ratio of the activated filler to anhydrous toluene was 1:25, the amount of 3-propyltriethoxysilane was 13 wt% of the mass of the activated filler, and the amount of dibutyltin dilaurate was 0.8 wt% of the mass of 3-propyltriethoxysilane. A3. The coupling intermediate was dispersed in dry N,N-dimethylformamide, and hydroxyl-polyethylene glycol-acrylate was added. The mixture was stirred at 500 rpm and reacted at 65°C for 7.5 h. After centrifugation at 7000 rpm for 8 min, the mixture was washed three times with N,N-dimethylformamide and vacuum dried at -0.085 MPa and 55°C for 15 h to obtain the modified filler. The solid-liquid ratio of the coupling intermediate to N,N-dimethylformamide was 1:15, and the amount of hydroxyl-polyethylene glycol-acrylate was 25 wt% of the mass of the coupling intermediate. The modified lithium salt is prepared by the following steps: B1. Under a nitrogen atmosphere, 4-vinylbenzenesulfonamide was dissolved in anhydrous tetrahydrofuran, cooled to 4°C in an ice bath, and sodium hydride was added in portions at 6-minute intervals. After the addition was complete, the mixture was heated to room temperature and stirred at 350 rpm for 2.5 h to obtain the active precursor. The amount of sodium hydride was 13.8 wt% of the mass of 4-vinylbenzenesulfonamide, and the amount of anhydrous tetrahydrofuran was 14 times the mass of 4-vinylbenzenesulfonamide. B2. Add an anhydrous N,N-dimethylformamide solution of 1,3-propanesulfonate lactone to the active precursor, stir at 55°C for 15 h with stirring at 350 rpm, cool, filter, and dry at 72°C for 7.5 h to obtain the sulfonated intermediate; wherein the amount of 1,3-propanesulfonate lactone is 77 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, and the amount of N,N-dimethylformamide is 5 times the mass of 1,3-propanesulfonate lactone; B3. The sulfonated intermediate is suspended in deionized water, lithium carbonate is added, and the mixture is stirred at room temperature for 2.5 h at 350 rpm. The mixture is filtered, and the filtrate is concentrated under reduced pressure at 65 °C. The filtrate is then vacuum dried at -0.085 MPa and 72 °C for 15 h to obtain the modified lithium salt. The amount of lithium carbonate used is 23 wt% of the mass of 4-vinylbenzenesulfonamide in step B1.
[0035] A method for preparing a composite solid electrolyte material includes the following steps: S1. Polyethylene oxide, modified lithium salt, succinate and initiator are dissolved in an organic solvent and stirred at 425 rpm for 1.8 h to obtain a mixed solution; wherein, the organic solvent is N,N-dimethylformamide, the initiator is azobisisobutyronitrile, the amount of initiator added is 1.5 wt% of the mass of polyethylene oxide, and the stirring and dissolution temperature is 45℃; S2. Add the modified filler to the mixed solution and ultrasonically disperse it for 1.5 hours at 400W power to obtain a slurry; S3. The slurry is cast onto a substrate, dried, and peeled off to obtain the composite solid electrolyte material; wherein the drying temperature is 85°C, the time is 14h, and the vacuum degree is -0.085MPa.
[0036] Example 5
[0037] A composite solid electrolyte material comprises the following raw materials in parts by weight: 85 parts polyethylene oxide, 15 parts modified filler, 30 parts modified lithium salt, and 10 parts succinic anionyl nitrile. The modified filler is prepared by the following steps: A1. Tantalum-doped lithium lanthanum zirconium oxide was dispersed in hydrochloric acid aqueous solution, ultrasonicated at 500W for 30 min, centrifuged at 8000 rpm for 5 min, washed with deionized water until neutral 4 times, and vacuum dried at -0.08 MPa and 150℃ for 2 h to obtain activated filler; wherein the tantalum-doped lithium lanthanum zirconium oxide had a particle size D50 of 500 nm, a specific surface area of 5 m² / g, and an ionic conductivity of 3 × 10⁻⁶. -4 S / cm, the concentration of hydrochloric acid aqueous solution is 1.0 mol / L, and the solid-liquid ratio of tantalum-doped lithium lanthanum zirconium oxide to hydrochloric acid aqueous solution is 1:20; A2. Under nitrogen protection, the activated filler was dispersed in anhydrous toluene, and 3-propyltriethoxysilane and dibutyltin dilaurate were added. The mixture was stirred at 600 rpm and reacted at 80°C for 4 h. Under nitrogen protection, the mixture was centrifuged at 8000 rpm for 5 min and washed three times with anhydrous toluene to obtain the coupling intermediate. The solid-liquid ratio of the activated filler to anhydrous toluene was 1:20, the amount of 3-propyltriethoxysilane was 15 wt% of the mass of the activated filler, and the amount of dibutyltin dilaurate was 1.0 wt% of the mass of 3-propyltriethoxysilane. A3. The coupling intermediate was dispersed in dry N,N-dimethylformamide, and hydroxyl-polyethylene glycol-acrylate was added. The mixture was stirred at 600 rpm and reacted at 70°C for 6 h. After centrifugation at 8000 rpm for 5 min, the mixture was washed three times with N,N-dimethylformamide and vacuum dried at -0.08 MPa and 60°C for 12 h to obtain the modified filler. The solid-liquid ratio of the coupling intermediate to N,N-dimethylformamide was 1:10, and the amount of hydroxyl-polyethylene glycol-acrylate was 30 wt% of the mass of the coupling intermediate. The modified lithium salt is prepared by the following steps: B1. Under a nitrogen atmosphere, 4-vinylbenzenesulfonamide was dissolved in anhydrous tetrahydrofuran, cooled to 5°C in an ice bath, and sodium hydride was added in portions at 5-minute intervals. After the addition was complete, the mixture was heated to room temperature and stirred at 400 rpm for 2 hours to obtain the active precursor. The amount of sodium hydride was 14 wt% of the mass of 4-vinylbenzenesulfonamide, and the amount of anhydrous tetrahydrofuran was 15 times the mass of 4-vinylbenzenesulfonamide. B2. Add an anhydrous N,N-dimethylformamide solution of 1,3-propanesulfonate lactone to the active precursor, stir at 60°C for 12 h with stirring at 400 rpm, cool, filter, and dry at 80°C for 6 h to obtain a sulfonated intermediate; wherein the amount of 1,3-propanesulfonate lactone is 80 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, and the amount of N,N-dimethylformamide is 6 times the mass of 1,3-propanesulfonate lactone; B3. The sulfonated intermediate is suspended in deionized water, lithium carbonate is added, and the mixture is stirred at room temperature for 2 hours at 400 rpm. The mixture is filtered, and the filtrate is concentrated under reduced pressure at 70°C. The filtrate is then vacuum dried at -0.08 MPa and 80°C for 12 hours to obtain the modified lithium salt. The amount of lithium carbonate used is 24 wt% of the mass of 4-vinylbenzenesulfonamide in step B1.
[0038] A method for preparing a composite solid electrolyte material includes the following steps: S1. Polyethylene oxide, modified lithium salt, succinate and initiator are dissolved in an organic solvent and stirred at 500 rpm for 1 h to obtain a mixed solution; wherein, the organic solvent is N,N-dimethylformamide, the initiator is azobisisobutyronitrile, the amount of initiator added is 2 wt% of the mass of polyethylene oxide, and the stirring and dissolving temperature is 50℃. S2. Add the modified filler to the mixed solution and ultrasonically disperse it at 500W power for 1 hour to obtain a slurry; S3. The slurry is cast onto a substrate, dried, and peeled off to obtain the composite solid electrolyte material; wherein the drying temperature is 90℃, the time is 12h, and the vacuum degree is -0.08MPa.
[0039] Comparative Example 1 A method for preparing a composite solid electrolyte material, compared with the method for preparing the composite solid electrolyte material in Example 1, is mainly different in that: in this comparative example, an equal amount of tantalum-doped lithium lanthanum zirconium oxide is used instead of the modified filler, while the other components and preparation methods are completely consistent with those in Example 1.
[0040] Comparative Example 2 A method for preparing a composite solid electrolyte material, compared with the method for preparing the composite solid electrolyte material in Example 1, is mainly different in that: in this comparative example, an equal amount of lithium bis(trifluoromethanesulfonyl)imide is used instead of modified lithium salt, while the other components and preparation methods are completely consistent with those in Example 1.
[0041] Comparative Example 3 A method for preparing a composite solid electrolyte material, compared with the method for preparing a composite solid electrolyte material in Example 1, is mainly different in that: no initiator is added in step S1 of this comparative example, and the other components and preparation methods are completely consistent with those in Example 1.
[0042] Comparative Example 4 A method for preparing a composite solid electrolyte material, compared with the method for preparing the composite solid electrolyte material in Example 1, is mainly different in that: in this comparative example, an equal amount of tantalum-doped lithium lanthanum zirconium oxide is used instead of the modified filler, and an equal amount of lithium bis(trifluoromethanesulfonyl)imide is used instead of the modified lithium salt. Other components and preparation methods are completely consistent with those in Example 1.
[0043] Comparative Example 5 A method for preparing a composite solid electrolyte material, compared with the method for preparing the composite solid electrolyte material in Example 1, is mainly different in that: in this comparative example, no initiator is added in step S1, and an equal amount of unmodified tantalum-doped lithium lanthanum zirconium oxide is used instead of the modified filler, and an equal amount of lithium bis(trifluoromethanesulfonyl)imide is used instead of the modified lithium salt. Other components and preparation methods are completely consistent with those in Example 1.
[0044] The hydroxyl-polyethylene glycol-acrylate used in the examples and comparative examples of this invention was purchased from Shaanxi Xingbei Aike Biotechnology Co., Ltd., model number XB-19; other undisclosed reagents were all commercially available.
[0045] Performance testing: The electrolyte materials obtained in Examples 1-5 and Comparative Examples 1-5 were subjected to the following relevant performance tests, and the test results are shown in Table 1: (1) Ionic conductivity: The composite solid electrolyte material is sandwiched between two stainless steel blocking electrodes to form a blocking battery. The battery is tested by AC impedance spectroscopy at 25°C with a frequency range of 1Hz-1MHz and a perturbation amplitude of 10mV. The ionic conductivity is calculated by formula σ=L / (R×S), where L is the thickness of the electrolyte material, which is 80μm, R is the bulk resistance, and S is the effective contact area. (2) Lithium-ion transference number: A composite solid electrolyte material was sandwiched between two lithium metal electrodes to assemble a lithium symmetric battery. The battery was tested at 25°C using the Bruce-Vincent method. A DC polarization voltage of 10mV was applied to the battery, and the initial current and steady-state current were recorded. The interfacial impedance was measured before and after polarization to obtain the interfacial impedance value, and the value was calculated according to the formula tLi. + =[Is×(ΔV-I0×R0)] / [I0×(ΔV-Is×Rs)] calculates the lithium-ion transference number, where I0 and Is are the initial current and steady-state current, respectively, R0 and Rs are the interface impedances before and after polarization, respectively, and ΔV is the applied DC polarization voltage; (3) Cyclic capacity retention rate: The composite solid electrolyte material is assembled into a full battery with lithium metal anode and lithium iron phosphate cathode. The constant current charge-discharge cycle test is carried out at 25°C at a rate of 0.5C. The charge-discharge voltage window is 2.5-4.0V. The ratio of the discharge capacity of the 200th cycle to the discharge capacity of the first cycle is recorded, which is the cycle capacity retention rate.
[0046]
[0047] As shown in Table 1, Examples 1-5 significantly outperformed the comparative examples in terms of ionic conductivity, lithium-ion transference number, and cycle capacity retention. Comparative Example 1 used unmodified filler, which lacked polyether graft chains and acrylate groups on its surface, resulting in only physical contact with the polyethylene oxide matrix. This led to high interfacial impedance and the inability to participate in in-situ crosslinking to construct a covalent network, resulting in significantly lower ionic conductivity and cycle capacity retention compared to Example 1. Comparative Example 2 used conventional lithium salt, allowing free migration of anions, resulting in a low lithium-ion transference number, severe concentration polarization, and compromised cycle stability. Comparative Example 3 did not include an initiator. Although the modified filler and modified lithium salt contained acrylate groups and styrene double bonds, in-situ crosslinking was impossible. The system exhibited only physical entanglement without a chemically bonded network, and its overall performance was far inferior to Example 1, indicating that in-situ crosslinking is crucial for constructing a stable interface and immobilizing anions. Comparative Example 4 used unmodified filler and conventional lithium salt. Although it contained an initiator, it lacked double bond substrates, preventing crosslinking reactions from occurring. The filler-matrix interface showed weak bonding and free migration of anions, resulting in low levels of all three indicators. Comparative Example 5 was a completely traditional physical blend system, without modified components or initiators, and its three indicators were the lowest among all cases.
[0048] This demonstrates that the present invention, through the synergistic effect of the acrylate groups on the surface of the modified filler and the styrene double bonds of the modified lithium salt in the in-situ crosslinking system, constructs a synergistic network of filler-matrix chemical bonding and anion covalent anchoring in situ under the action of an initiator. This significantly improves lithium-ion transference number and cycle stability while enhancing ionic conductivity, achieving simultaneous optimization of multiple electrochemical properties. The technical effect is significantly better than that of existing technical solutions.
[0049] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0050] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A composite solid electrolyte material, characterized in that, The raw materials include the following parts by weight: 60-85 parts polyethylene oxide, 5-15 parts modified filler, 10-30 parts modified lithium salt, and 1-10 parts butadiene nitrile. The modified filler is prepared by the following steps: A1. Tantalum-doped lithium lanthanum zirconium oxide is dispersed in hydrochloric acid aqueous solution, ultrasonically treated, centrifuged, washed until neutral, and vacuum dried to obtain activated filler; A2. Under nitrogen protection, the activated filler was dispersed in anhydrous toluene, and 3-propyltriethoxysilane and dibutyltin dilaurate were added. The mixture was stirred and reacted, then centrifuged and washed under nitrogen protection to obtain the coupling intermediate. A3. Disperse the coupling intermediate in dry N,N-dimethylformamide, add hydroxyl-polyethylene glycol-acrylate, stir to react, centrifuge, wash, and vacuum dry to obtain the modified filler; The modified lithium salt is prepared by the following steps: B1. Under a nitrogen atmosphere, 4-vinylbenzenesulfonamide was dissolved in anhydrous tetrahydrofuran, cooled in an ice bath, and sodium hydride was added in portions. After the addition was complete, the mixture was heated to room temperature and stirred to obtain the active precursor. B2. Add an anhydrous N,N-dimethylformamide solution of 1,3-propanesulfonic acid lactone to the active precursor, heat and stir the reaction, cool, filter, and dry to obtain the sulfonated intermediate; B3. The sulfonated intermediate is suspended in deionized water, lithium carbonate is added, the mixture is stirred at room temperature, filtered, the filtrate is concentrated under reduced pressure and dried under vacuum to obtain the modified lithium salt.
2. The composite solid electrolyte material according to claim 1, characterized in that, In step A1, the concentration of the hydrochloric acid aqueous solution is 0.1-1.0 mol / L, the ultrasonic treatment time is 30-60 min, the vacuum drying temperature is 120-150℃, the time is 2-4 h, and the solid-liquid ratio of tantalum-doped lithium lanthanum zirconium oxide to hydrochloric acid aqueous solution is 1:(20-50).
3. The composite solid electrolyte material according to claim 1, characterized in that, In step A2, the stirring reaction is carried out at a temperature of 60-80℃ for 4-8 hours, the solid-liquid ratio of the activated filler to anhydrous toluene is 1:(20-40), the amount of 3-propyltriethoxysilane used is 5-15 wt% of the mass of the activated filler, and the amount of dibutyltin dilaurate used is 0.1-1.0 wt% of the mass of 3-propyltriethoxysilane.
4. The composite solid electrolyte material according to claim 1, characterized in that, In step A3, the stirring reaction is carried out at a temperature of 50-70°C for 6-12 hours, the vacuum drying is carried out at a temperature of 40-60°C for 12-24 hours, the solid-liquid ratio of the coupling intermediate to N,N-dimethylformamide is 1:(10-30), and the amount of hydroxyl-polyethylene glycol-acrylate is 10-30 wt% of the mass of the coupling intermediate.
5. The composite solid electrolyte material according to claim 1, characterized in that, In step B1, the amount of sodium hydride used is 13-14 wt% of the mass of 4-vinylbenzenesulfonamide, the amount of anhydrous tetrahydrofuran used is 8-15 times the mass of 4-vinylbenzenesulfonamide, and the reaction time is 2-4 h with stirring at room temperature.
6. The composite solid electrolyte material according to claim 1, characterized in that, In step B2, the amount of 1,3-propanesulfonic acid lactone is 67-80 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, and the amount of N,N-dimethylformamide is 3-6 times the mass of 1,3-propanesulfonic acid lactone. The temperature for heating and stirring the reaction is 40-60°C, and the time is 12-24 h.
7. The composite solid electrolyte material according to claim 1, characterized in that, In step B3, the amount of lithium carbonate used is 20-24 wt% of the mass of 4-vinylbenzenesulfonamide in step B1, the reaction time is 2-4 h with stirring at room temperature, and the vacuum drying temperature is 50-80 °C for 12-24 h.
8. A method for preparing a composite solid electrolyte material, characterized in that, Includes the following steps: S1. Dissolve polyethylene oxide, modified lithium salt, succinate and initiator in an organic solvent, stir to dissolve, and obtain a mixed solution; S2. Add the modified filler to the mixed solution and disperse it to obtain a slurry; S3. The slurry is cast onto a substrate, dried, and then peeled off to obtain the composite solid electrolyte material.
9. The method for preparing the composite solid electrolyte material according to claim 8, characterized in that, In step S1, the organic solvent is N,N-dimethylformamide, the initiator is azobisisobutyronitrile, the amount of initiator added is 0.1-2 wt% of the mass of polyethylene oxide, and the stirring and dissolving temperature is 30-50℃.
10. The method for preparing the composite solid electrolyte material according to claim 8, characterized in that, In step S3, the drying process is carried out at a temperature of 70-90°C for 12-20 hours and at a vacuum level of -0.08 to -0.1 MPa.
Citation Information
Patent Citations
Solid-state electrolyte sheet and method for manufacturing the same
CN121790492B